Case report: complete long-lasting response to multimodal third line treatment with neurosurgical resection, carmustine wafer implantation and dabrafenib plus trametinib in a BRAFV600E mutated high-grade glioma - Castelli, Barbara; Tellini, Marco; Guidi, Melina; Di Nicola, Marco; Giunti, Laura; Buccoliero, Anna Maria; Censullo, Maria Luigia; Iacono, Alessandro; Desideri, Isacco; Genitori, Lorenzo; Sardi, Iacopo; Fonte, Carla (Frontiers in Oncology, 2024)
Dabrafenib plus trametinib is a promising new therapy for patients affected by BRAFV600E-mutant glioma, with high overall response and manageable toxicity. We described a complete and long-lasting response in a case of recurrent anaplastic pleomorphic xanthoastrocytoma CNS WHO-grade 3 BRAFV600E mutated. Due to very poor prognosis, there are a few described cases of high-grade glioma (HGG) patients treated with the combined target therapy as third-line treatment. The emergence of optimized sequencing strategies and targeted agents, including multimodal and systemic therapy with dabrafenib plus trametinib, will continue to broaden personalized therapy in HGG improving patient outcomes.